Electroencephalographic criteria of the functional outcome prognosis in the acute period of spontaneous supratentorial intracerebral hemorrhage - Koziolkin, О. А.; Kuznietsov, А. А.; Козьолкін, Олександр Анатолійович; Кузнєцов, Антон Анатолійович; Козёлкин, А. А.; Кузнецов, А. А. (Запорізький державний медичний університет, 2020)
The aim of this study was to define electroencephalographic predictors of unfavorable functional outcome of spontaneous supratentorial intracerebral hemorrhage (SSICH) in the acute period. Materials and methods. Prospective, cohort and comparative study was conducted in 114 patients (mean age 67.4 ± 0.8 years) in the acute period of SSICH. Electroencephalography (EEG) was conducted on the 1st–2nd day of the disease. The values of relative band spectral powers of delta rhythm (0.5–4.0 Hz), theta (4–8 Hz), alpha (8–13 Hz), beta (13–35 Hz), theta1 (4–6 Hz), theta2 (6–8 Hz), alpha1 (8–10 Hz), alpha2 (10–13 Hz), beta1 (13–25 Hz) and beta2 (25–35 Hz) were determined in the affected and intact hemispheres. The fronto-occipital rhythm gradient and the severity of interhemispheric rhythm asymmetry were calculated. The functional outcome of the disease in the acute period was assessed on day 21 based on the modified Rankin Scale (mRS), and the value of mRS score >3 was considered as an unfavorable functional outcome. Results. Unfavorable functional outcome of the SSICH in the acute period was registered in 53 (46.5 %) patients. Independent association with the risk of unfavorable functional outcome of SSICH in the acute period was proved for the following indexes of the spectral analysis of EEG pattern in the first 2 days from the onset of the disease: the relative delta band spectral power in the affected hemisphere (OR (95 % CI) = 1.18 (1.11–1.25), P ˂ 0.0001) and the fronto-occipital rhythm gradient of beta band in the affected hemisphere (OR (95 % CI) = 0.0007 (0.0001–0.0293), P = 0.0001). These predictors were integrated in the mathematical model for the determination of an individual risk of unfavorable functional outcome of SSICH in the acute period (AUC (95 % CI) = 0.94 (0.88–0.98), P ˂ 0.0001; forecast accuracy = 87.7 %). Conclusions. Bilateral shift of EEG spectral power pattern of rhythms towards slow-wave activity of the hemisphere with the formation of interhemispheric asymmetry of delta band rhythms in the frontal areas, bilateral reduction in zonal differences of alpha band rhythms, the inversion of the fronto-occipital rhythm gradient of beta band in the affected hemisphere and the reduction in zonal differences of beta band rhythms due to beta2 band in the intact hemisphere with the formation of multidirectional interhemispheric asymmetry in the frontal and occipital parts of the brain in the first 2 days upon the onset of SSICH are considered as EEG criteria for unfavorable functional outcome of the disease in the acute period. Мета роботи – визначити електроенцефалографічні предиктори несприятливого функціонального результату гострого періоду спонтанного супратенторіального внутрішньомозкового крововиливу (ССВМК). Матеріали та методи. Здійснили проспективне, когортне, порівняльне дослідження 114 пацієнтів (середній вік – 67,4 ± 0,9 року) в гострому періоді ССВМК на тлі консервативної терапії. Рівень неврологічного дефіциту оцінювали за National Institute of Health Stroke Scale. Електроенцефалографічне (ЕЕГ) дослідження виконали в перші 2 доби захворювання. Окремо для ураженої та інтактної гемісфер визначали рівні відносної спектральної потужності ритмів дельта- (0,5–4,0 Гц), тета- (4–8 Гц), альфа- (8–13 Гц), бета (13–35 Гц) діапазонів, тета1- (4–6 Гц), тета2- (6–8 Гц), альфа1- (8–10 Гц), альфа2- (10–13 Гц), бета1- (13–25 Гц) і бета2- (25–35 Гц) піддіапазонів, а також лобово-потиличні градієнти, вираженість міжпівкульової асиметрії ритмів. Функціональний результат гострого періоду ССВМК оцінювали на 21 добу захворювання за модифікованою шкалою Ренкіна (мШР), несприятливий функціональний наслідок – у разі значення >3 балів за мШР. Результати. Несприятливий функціональний результат зареєстрували в 53 (46,5 %) пацієнтів. Незалежна асоціація з ризиком несприятливого функціонального наслідку гострого періоду ССВМК доведена для таких показників спектрального аналізу ЕЕГ-патерну в перші 2 доби від дебюту захворювання: відносна спектральна потужність ритмів дельта-діапазону ураженої гемісфери (ВШ (95 % ДІ) = 1,18 (1,11–1,25), р ˂ 0,0001), лобово-потиличний градієнт ритмів бета-діапазону ураженої гемісфери (ВШ (95 % ДІ) = 0,0007 (0,0001–0,0293), р = 0,0001). Ці предиктори інтегровані в математичну модель для визначення індивідуального ризику несприятливого функціонального результату гострого періоду ССВМК (AUC (95 % ДІ) = 0,94 (0,88–0,98), р ˂ 0,0001; точність прогнозування = 87,7 %). Висновки. Білатеральний зсув спектральної потужності ритмів ЕЕГ-патерну в бік повільнохвильової активності з формуванням міжпівкульової асиметрії ритмів дельта-діапазону у фронтальних відділах, білатеральна редукція зональних відмінностей ритмів альфа-діапазону, інверсія лобово-потиличного градієнта ритмів бета-діапазону в ураженій гемісфері та редукція зональних відмінностей ритмів бета-діапазону через бета2-піддіапазон в інтактній гемісфері з формуванням різноспрямованої міжпівкульової асиметрії цих ритмів у фронтальних і каудальних відділах головного мозку в перші 2 доби від дебюту ССВМК – електроенцефалографічні критерії несприятливого функціонального прогнозу результату гострого періоду захворювання. Цель работы – определить электроэнцефалографические предикторы неблагоприятного функционального исхода острого периода спонтанного супратенториального внутримозгового кровоизлияния (ССВМК). Материалы и методы. Проведено проспективное, когортное, сравнительное исследование 114 пациентов (средний возраст – 67,4 ± 0,9 года) в остром периоде ССВМК на фоне консервативной терапии. Уровень неврологического дефицита оценивали по National Institute of Health Stroke Scale. Электроэнцефалографическое (ЭЭГ) исследование выполнили в первые 2 суток заболевания. Отдельно для пораженной и интактной гемисфер определяли уровни относительной спектральной мощности ритмов дельта- (0,5–4,0 Гц), тета- (4–8 Гц), альфа- (8–13 Гц), бета- (13–35 Гц) диапазонов, тета1- (4–6 Гц), тета2- (6–8 Гц), альфа1- (8–10 Гц), альфа2- (10–13 Гц), бета1- (13–25 Гц) и бета2- (25–35 Гц) поддиапазонов, а также лобно-затылочные градиенты и выраженность межполушарной асимметрии ритмов. Функциональный исход острого периода ССВМК оценивали на 21 сутки заболевания по модифицированной шкале Рэнкина (мШР), неблагоприятный функциональный исход – при значении >3 баллов по мШР. Результаты. Неблагоприятный функциональный исход зарегистрирован у 53 (46,5 %) пациентов. Независимая ассоциация с риском неблагоприятного функционального исхода острого периода ССВМК доказана для таких показателей спектрального анализа ЭЭГ-паттерна в первые 2 суток от дебюта заболевания: относительная спектральная мощность ритмов дельта-диапазона в пораженной гемисфере (ОШ (95 % ДИ) = 1,18 (1,11–1,25), р ˂ 0,0001), лобно-затылочный градиент ритмов бета-диапазона в пораженной гемисфере (ОШ (95 % ДИ) = 0,0007 (0,0001–0,0293), р = 0,0001). Эти предикторы интегрированы в математическую модель для определения индивидуального риска неблагоприятного функционального исхода острого периода ССВМК (AUC (95 % ДИ) = 0,94 (0,88–0,98), р ˂ 0,0001, точность прогнозирования = 87,7 %). Выводы. Билатеральное смещение спектральной мощности ритмов ЭЭГ-паттерна в сторону медленноволновой активности с формированием межполушарной асимметрии ритмов дельта-диапазона во фронтальных отделах, билатеральная редукция зональных различий ритмов альфа-диапазона, инверсия лобно-затылочного градиента ритмов бета-диапазона в пораженной гемисфере и редукция зональных различий ритмов бета-диапазоне за счет бета2-поддиапазона в интактной гемисфере с формированием разнонаправленной межполушарной асимметрии указанных ритмов в передних и каудальных отделах головного мозга в первые 2 суток от дебюта ССВМК – ЭЭГ-критерии неблагоприятного функционального прогноза исхода острого периода заболевания.
Електроенцефалографічні критерії прогнозу функціонального результату гострого періоду спонтанного супратенторіального внутрішньомозкового крововиливу
Электроэнцефалографические критерии прогнозирования функционального исхода острого периода спонтанного супратенториального внутримозгового кровоизлияния
Keywords: cerebral hemorrhage; electroencephalography; prognosis; внутрішньомозковий крововилив; електроенцефалографія; прогноз; внутримозговое кровоизлияние; электроэнцефалография